The Addition of Lamtoro Leaf Fermented (Leucaena leucocephala) in Artificial Feed Against the Growth of Milkfish (Chanos chanos) - Harefa, Fendi Saputra; Khalil, Munawwar; Salamah, Salamah; Mainisa, Mainisa; Mahdaliana, Mahdaliana (Jurnal Ilmiah Samudra Akuatika, 2023)
Milkfish is a leading commodity for Indonesian mariculture which is quite promising, so milkfish productivity must be increased. The problematic factor in cultivating milkfish is feed. Lamtoro leaves (Leucaena leucocephala) are a potential biological resource and have high protein content as a raw material for making feed. However, lamtoro has a high fiber content which can be reduced by fermenting using bio intan tani and attractants to cover the aroma of lamtoro which fish do not like. This research aims to test the effect of adding fermented lamtoro leaves to artificial feed on the growth of milkfish. The research was carried out on March 22 - April 22 2022 at Kembang Tani Farm Lancang Barat, North Aceh, Aceh. The research used a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, Treatments A, B, C and D with concentrations of 0%, 15%, 20% and 25% respectively. Based on the F test analysis (ANOVA), the results gave a significant effect on feed response, weight gain, length increase, aroma with a Sig value < 0.05 and gave results that had no real effect on survival rate and feed conversion value with a Sig value > 0. 05.